PERSPEKTIF ISLAM DALAM ENTERPRENEUR - Syuhri, Saifuddin (Finance : Journal of Accounting and Finance, 2023)
Entrepreneurship in the Islamic perspective is not merely considered an economic activity but also an act of worship and a means to attain life’s blessings. Islam encourages its followers to be productive, creative, and independent individuals who earn a living through lawful (halal) and wholesome (thayyib) business activities. Core values such as honesty (ṣidq), responsibility (amanah), diligence (ijtihād), and justice (‘adl) form the foundation of Islamic entrepreneurial practice. This article aims to explore the principles of entrepreneurship in Islam and how these values are applied in modern business contexts. Using a qualitative approach through literature review, this study concludes that entrepreneurship based on Islamic values can foster an ethical, sustainable, and socially beneficial business ecosystem.